2010
DOI: 10.58799/ofr-521
|View full text |Cite
|
Sign up to set email alerts
|

Multi-tracer investigation of groundwater residence time in a karstic aquifer: Bitter Lake National Wildlife Refuge, New Mexico, USA

Abstract: Several natural and anthropogenic tracers have been used to evaluate groundwater residence time within a karstic limestone aquifer in southeastern New Mexico, USA. Natural groundwater discharge occurs in the lower Pecos Valley from a region of karst springs, wetlands and sinkhole lakes at Bitter Lake National Wildlife Refuge,on the northeast margin of the Roswell Artesian Basin. The springs and sinkholes are formed in gypsum bedrock that serves as a leaky confining unit for an artesian aquifer in the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Additionally, the Bitter Creek site (BC-LRC) was a net producer of G. desperatus migrants for Sago Spring sites (SS and S-31). While the groundwater sources for Bitter Creek and Sago Spring seem to be distinct and independent (Lang 1998), the overland distance between these locations is less than 0.5 km, with a river distance between the two sites just over 2 km. While little information is available regarding dispersal of these species, passive dispersal may occur via birds for both snails (Ponder et al 1989(Ponder et al , 1994 and amphipods (Rachalewski et al 2013), while groundwater connections have been shown to facilitate dispersal in amphipods (Harris et al 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, the Bitter Creek site (BC-LRC) was a net producer of G. desperatus migrants for Sago Spring sites (SS and S-31). While the groundwater sources for Bitter Creek and Sago Spring seem to be distinct and independent (Lang 1998), the overland distance between these locations is less than 0.5 km, with a river distance between the two sites just over 2 km. While little information is available regarding dispersal of these species, passive dispersal may occur via birds for both snails (Ponder et al 1989(Ponder et al , 1994 and amphipods (Rachalewski et al 2013), while groundwater connections have been shown to facilitate dispersal in amphipods (Harris et al 2002).…”
Section: Discussionmentioning
confidence: 86%
“…The refuge lies over an area of karst topography and natural groundwater discharge that originates from the Roswell Artesian Basin and manifests as numerous sinkholes, seeps, springs, and associated wetlands (Land & Huff 2010). Subsurface layers of gypsum (CaSO 4 ) and halite (NaCl) in this basin enrich groundwater discharge with ion concentrations, ranging from 1.83 to 6.81 ppt in springs and 38.45 to 86.978 ppt in sinkholes (Land & Huff 2010;Partey et al 2008).…”
Section: Study Areamentioning
confidence: 99%
“…The refuge lies over an area of karst topography and natural groundwater discharge that originates from the Roswell Artesian Basin and manifests as numerous sinkholes, seeps, springs, and associated wetlands (Land & Huff 2010). Subsurface layers of gypsum (CaSO 4 ) and halite (NaCl) in this basin enrich groundwater discharge with ion concentrations, ranging from 1.83 to 6.81 ppt in springs and 38.45 to 86.978 ppt in sinkholes (Land & Huff 2010;Partey et al 2008). The region's hydrogeology in combination with the overlying mixed features of the Chihuahuan Desert and the southern Great Plains, shape a system of desert uplands and wetland habitats that sustain one of the most unique and biodiverse places in the southwestern United States (Johnson et al 2003).…”
Section: Study Areamentioning
confidence: 99%
“…Most of the work presented here focuses on these sinkholes and the springs that lie within and south of BLNWR. A detailed description of the geology and hydrology of the Bitter Lake Quadrangle has been documented by Land and McCraw and their colleagues (Land, 2005;McCraw et al, 2007;Land and Huff, 2010a;2010b).…”
Section: Study Areamentioning
confidence: 99%
“…Water bodies such as the sinkholes, springs and lakes at Bitter Lake National Wildlife Refuge (BLNWR) provide habitat for a number of threatened and endangered species. These features are formed in gypsum bedrock, which serves as a leaky confining unit for an artesian aquifer in the underlying San Andres limestone, and are fed by upward seepage of groundwater from the aquifer (Land and Huff, 2010a;2010b). However, the processes that control or influence groundwater quality at Bitter Lake are poorly understood.…”
Section: Introductionmentioning
confidence: 99%